Influence of Mobbing (Workplace Bullying) on Depressive Symptoms: A Longitudinal Study Among Employees Working with People with Intellectual Disabilities - Olivares-Faundez, V (Blackwell Publishing Ltd, 2015)
Background: The problem of mobbing has attracted a great deal of attention over the past few years. This concern has increased the study of the phenomena, which has resulted in many scientific publications. Mobbing has been characterised as an emerging risk at work. The aim of this longitudinal study was to analyse the influence of mobbing on depressive symptoms in a sample of employees working with people with intellectual disabilities (ID). Method: The sample consisted of 372 Spanish employees working with people with ID at 61 job centres in the Valencian Community (Spain). Seventy-nine (21.2%) participants were men, and 293 were (78.8%) women. Mobbing was evaluated by the Mobbing-UNIPSICO scale, and depressive symptoms were measured using the Zung Self Rating Depression Scale. Using analyses of variance (anova), we tested the differences in depressive symptoms according to the mobbing criteria indicated by Leymann, that is, frequency and duration at Time 1 and Time 2. Results: Employees who met the mobbing criteria: frequency (at least once a week) and duration (at least 6 months) at the two study times presented significantly higher levels of depressive symptoms than employees who met mobbing criteria at Time 1, but did not meet any criteria for mobbing at Time 2, and employees who did not meet any criteria for mobbing at Time 1 or Time 2. Conclusions: We conclude that permanence of mobbing from Time 1 to Time 2 increases depressive symptoms. © 2015 John Wiley & Sons Ltd.